PERLINDUNGAN HUKUM ATAS KARYA CIPTA PROGRAM KOMPUTER DI INDONESIA (STUD! PERBANDINGAN DENGAN NEGARA MAJU DAN NEGARA BERKEMBANG) - Ni Ketut Supasti Dharmawan (Faculty of Law, Universitas Diponegoro, 2011)
The type of this research is socio legal research which employed hermeneutic approach. The study showed that the legal protection of Computer Program which is regulated under Copyrights Act No. 19 Year 2002 is still weak in Indonesia. Based on BSA and USSTR report 2009, Indonesia was considered still in level of Priority Watch List. Some factors caused high level infringement of Computer Program (88%) in Indonesia due to: first, the legal substance of Computer Program protection (Article 15 (e) (g) the Act No. 19, Year 2002 concerning Copyright as the result of TRIPs harmonization, considered still distinct from the perspective legal culture of Indonesia. There are almost no space for social function (Copyright limitation) for Computer Program; Second, the factor of economic; Third, apparently the law enforcer more protect people who have power than the weak of end users; fourth, the innovation of technology. By comparing the legal protection with the developed countries (the European and US) and developing country (Malaysia),which are all as the member of WTO, only European regulate the Copyright limitation for Computer Program especially for education purposes such as to improve the technical emx» of Computer Program. Therefore the model of Article 5 (3) the Council Directive 911250/EEC of 14 May 1991 on the legal Protection of Computer Program, may suit with the need to construct Better future protection for Computer Program in Indonesia, regarding balance rights both for end users and the copyright owners.